Paisagem cultural em Itaúnas (ES) : o lugar e sua dimensão simbólica - Costa, Maísa Fávero (2017)
The concept of cultural landscape go through several science fields, being discussed in the fields of Geography, Architecture, Urbanism, as examples, and specifically in Cultural Heritage field. Its extent presuppose an approach of immaterial and material